The battle between HF and UHF RFID - F., Mohd-Yasin; M. K., Khaw; F., Choong; M. B. I., Reaz (HORIZON HOUSE PUBLICATIONS INC, 2008)
It is undeniable that RFID tags reign over the bar coding technologies and other optically read technologies due to its contactless nature, larger memory capacity and ability to allow energy to penetrate certain goods that are hidden or covered with substances such as snow, fog, ice, dirt, paint or crusted grime. In this article, the frequencies used in different RFID systems are compared. The frequencies can be divided into low frequency (LF), high frequency (HF), ultra high frequency (UHF) and microwave. The two most popular frequencies used in today's applications are HF and UHE HF refers to the frequency 13.56 MHz, while UHF refers to thefrequency range fi-oin 860 to 956 MHz. in the radio spectrum. Which is the better one?.